Building Students’ Character through Prophetic Education at Madrasa - Citra Putri Sari; Husniyatus Salamah Zainiyati; Rudy Al Hana (Jurnal Pendidikan Islam, 2020)
Several cases of juveniles have to some extent dominated mass media news recently and this worrying reality is contradictory to the purpose of education that teenagers are expected to achieve. In an attempt to solve this problem, various efforts have been made by educators and one of them is to promote prophetic-based education. This study was aimed at investigating prophetic education at Madrasa Muallimin/Muallimat (MMA) Bahrul Ulum Tambak Beras, Jombang. This research is qualitative descriptive using models of Miles and Huberman analyses. The data collected were analyzed through several steps namely reduction, presentation, and data verification. The results showed that the prophetic education was applied in MMA through internalizing Islamic values for students in their learning process. When it comes to internalizing values, MMA referred and addressed the local culture to cultivate for students. This process has been built since the establishment of MMA so that it has built students’ character which in turn gradually form the identity of the MMA among the society where it exists.